TEACHERS AND STUDENTS’ NET PROMOTER SCORE (NPS) ON THE CAMBRIDGE LEARNING MANAGEMENT SYSTEM (CLMS) - emilius german; Disa Evawani Lestari (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2021)
Technology in Education has been widely used due to several reasons. Millennial students’ characteristic, which is technology savvy, is one of them. The Covid- 19 pandemic has also been leading us to use technology in managing the classroom massively. This study aims to identify teachers and students’ Net Promoter Score (NPS) on the Cambridge Learning Management System (CLMS). Mixed methods and an online survey using google platforms were used to collect both quantitative and qualitative data. Nine English lecturers and 69 university students who had used CLMS for teaching and learning English level B1 (CEFR) participated. The results show that the lecturers and students’ NPS are 11 and 13, respectively. They imply that CLMS is considered good, resulting in the possibility for the users to reuse the LMS in the future.  However, there is still room for improvement. Fixing technical problems is highly recommended to enhance the possibility for the user to use the installed LMS. Providing more training for teachers is also suggested.